PENGARUH PROFITABILITAS, KOMPENSASI EKSEKUTIF, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 - muchammad tri rinaldi; Sartika Wulandari; Muhammad Ali Ma'sum (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study was conducted to determine the factors that influence the dependent variable, namely tax avoidance. The independent variables used in this study are profitability, executive compensation and capital intensity. The research data used is secondary data taken from the annual report on the Indonesia Stock Exchange (IDX) for 2017-2020. The population of this research are property and real estate companies. Based on the purposive sampling method, the researches obtained 136 samples from 34 companies for 4 years, namely 2017-2020. This study uses panel data analysis techniques and Eviews program tools. The results obtained show that the executive compensation variable is a factor that influences the dependent variable in this study. Executive compensation has a significant positive effect. Meanwhile, the factors that do not affect tax avoidance are profitability and capital intensity variables.